Mediation as Means of Communication for Public Administration in Settling Administrative Disputes - Kułak-Krzysiak, Katarzyna; Śwital, Paweł (Review of European and Comparative Law, 2023)
Nowadays solutions are sought for public administration to involve citisens in decision-making as one of the ways of promoting the development of civil society and thus to foster democratic forms of government. Public administration is looking for efficient methods of resolving administrative disputes. Administrative mediation serving the purpose of ensuring proper communication between the parties to administrative proceedings is one of such methods. Mediation in public administration hinges upon the definition of communication rules. The aim of this paper is to define communication from the perspective of legal science and discuss its application in the administrative mediation proceedings. In this article, we discuss the essence, the subject matter and the object of mediation as well as the legal regulations governing the mediation procedure and consider the possibility of applying mediation to the administrative procedure, as exemplified by the related case law. The study has been conducted by means of the legal research methods, in particular the legal-dogmatic approach and the legal functionalism approach.